2022
DOI: 10.1055/s-0042-1759562
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy in the Head and Neck: A Summary of Uses and Application Techniques

Abstract: Negative pressure wound therapy (NPWT) has had an expanded role in the management of complex wounds including its increasing use for complex wounds in the head and neck region. Challenges for use in the head and neck region include variations in surface topography and the proximity of sensitive mouth, nose, ear, eye, and tracheal openings. Despite these challenges, NPWT has been used in the head and neck immediately following free flap surgery, to prepare wounds for skin grafting or local flaps, to treat orocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Our results show that TNPT can significantly decrease the frequency of dressing changes and shorten the healing time without serious adverse events. Mechanistically, NPWT could accelerate wound healing by increasing dermal and subdermal perfusion, continuously removing interstitial fluid, enhancing formation of granulation tissue, increasing vascularity, and decreasing bacterial counts 14,42,43 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results show that TNPT can significantly decrease the frequency of dressing changes and shorten the healing time without serious adverse events. Mechanistically, NPWT could accelerate wound healing by increasing dermal and subdermal perfusion, continuously removing interstitial fluid, enhancing formation of granulation tissue, increasing vascularity, and decreasing bacterial counts 14,42,43 …”
Section: Discussionmentioning
confidence: 99%
“…44,45 However, most of the relevant research has focused on the external fistula orifice, with only a limited number of studies having investigated treatment of the internal fistula orifice. 42,46 Loeck et al found that endoscopic vacuum therapy could promote closure of a PCF by treating the internal fistula orifice. 47 However, this was an isolated case report, and more studies are needed to validate the effectiveness of endoscopic vacuum therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These challenges are compounded by the increasing use of non-pharmacological interventions in the wound healing space, which may not pose the same degree of risk and are an attractive alternative ( Ongarora, 2022 ). An example of such a technology is Negative Pressure Wound Therapy, which has been shown to improve wound healing times in surgical and traumatic injuries ( De Pellegrin et al, 2023 ; Liebman et al, 2023 ). Additionally, although studies claim that the cost of these wound healing peptides would be low, currently approved peptide drugs such as man-made insulin often come with significant price tags that are a cause of noncompliance amongst patients ( Chiang et al, 2023 ; Li et al, 2023 ).…”
Section: Challenges and Opportunities For Cyclic Wound Healing Peptidesmentioning
confidence: 99%